2020
DOI: 10.1007/978-3-030-58462-7_7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Railway Track Irregularities with Convolutional Autoencoders and Clustering Algorithms

Abstract: Modern maintenance strategies for railway tracks rely more and more on data acquired with low-cost sensors installed on in-service trains. This quasi-continuous condition monitoring produces huge amounts of data, which require appropriate processing strategies. Deep learning has become a promising tool in analyzing large volumes of sensory data. In this work, we demonstrate the potential of artificial intelligence to analyze railway track defects. We combine traditional signal processing methods with deep conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Niebling et al [ 371 ], staying in the mainstream of low-cost sensor applications—e.g., Knight-Percival et al [ 372 ]—on in-service trains, suggested deep learning ( artificial intelligence ) in order to analyze large volumes of sensors’ measurement data. The authors combined common signal processing methods and deep convolutional autoencoders and clustering algorithms.…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
“…Niebling et al [ 371 ], staying in the mainstream of low-cost sensor applications—e.g., Knight-Percival et al [ 372 ]—on in-service trains, suggested deep learning ( artificial intelligence ) in order to analyze large volumes of sensors’ measurement data. The authors combined common signal processing methods and deep convolutional autoencoders and clustering algorithms.…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
“…Recent work mainly made use of unsupervised machine learning methods and addressed e.g. the separation of vibration components caused by vehicle and rail using blind signal separation (16) or clustering of anomalies by usage of convolutional autoencoders (17) . In this paper, the set-up allows for supervised learning since the processed ABA data can be compared to reference data.…”
Section: Introductionmentioning
confidence: 99%
“…Mosleh et al [7] investigated an envelope spectral analysis approach to detect wheel flats with wayside sensors using a range of 3D simulations based on a train-track interaction model. In contrast to wayside systems, on-board monitoring systems have traditionally been focused on the detection of track defects [8][9][10][11][12] but are more and more considered for vehicle monitoring [13]. The advantage of on-board monitoring systems is that the wheel is monitored continuously and not only when the vehicle passes a track side monitoring site.…”
Section: Introductionmentioning
confidence: 99%